The Regulations for Management of Coastal Natural Resource Conflicts in Indonesia-Malaysia Border - Zein, Yahya Ahmad; Syaprillah, Aditia; Idris, Rafiq (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
Indonesia and Malaysia will continue to engage in violent and protracted border conflicts over natural resources due to limited natural resources. Due to the scarcity and abundance of renewable resources, there are border disputes between Indonesia and Malaysia. Illegal fishing is a concern for both countries. This study aimed to determine the management of Indonesia-Malaysia coastal natural resource disputes. This was normative legal research that employed statutory, empirical, and case methods. The study found that Indonesia and Malaysia need to strengthen their laws as a follow-up to their bilateral agreements, considering that illegal activities often occur along land and sea borders. Another problem is that maritime regulations in Indonesia and Malaysia have different problems and challenges, ranging from the lack of specific regulations to the existence of illegal activities on the sea and land borders of each country. The laws governing maritime sector activities are vulnerable to institutional conflicts due to overlapping regulations and legislation resulting from cross-border processing at maritime borders. Therefore, from a regulatory perspective, it is necessary to strengthen various existing regulations.